Ali je pravo pripravljeno na pametno pogodbo - Lampret, Leonardo Rok (Pravni letopis, 2021)
Smart contracts are one of the most important innovations that are part of blockchain technology. Due to the automatic execution of transactions and the guaranteed high level of anonymity, interest in the use of smart contracts is increasing. Considering that we find smart contracts in many legal relationships nowadays, they need to be properly regulated. In order to avoid legal pluralism, it is necessary to review the existing Slovenian legal order and ask whether the current legal regulation is sufficient to be able to use smart contracts in legal transactions efficiently and with a high degree of legal predictability. In doing so, it is particularly important that the contracting parties have a possibility to turn to the Court of law in order to efficiently protect their legal position. Due to the lack of case law, however, the contracting parties in the event of a dispute turn to a special form of arbitration, which operates on the blockchain technology.
Keywords: arbitraža; obligacijska razmerja; obligacijsko pravo; pametne pogodbe; pogodbe; pravno varstvo; sodno varstvo; tehnologija verižnih blokov